(untitled) (Heritage, 2022)
As a writer who read and followed the contemporary literature and literary theory in several different languages and who intensively contemplated the act of reading and thematised it in his belletristic prose, Kiš had already problematised in his novel The Attic the most important aspects of reading, brought to light and actualised by the classical literature and placed at the centre of research by the post-classical theory of narration: the first person narration and the problem of identity of the author’s I, the use of the trompe-l’œil technique, transgression of the narrative levels/narrative worlds and narrative metalepsis, the boundary between life and literature etc. The author of this paper focuses its research on the reader and the narrative metalepsis in Danilo Kiš’s first romanesque novel. The first part is dedicated to the definitions of narrative metalepsis in the contemporary theoretical studies (from Gérard Genette to John Pier), the second one to the types of metalepsis in The Attic, and the third one to the Kiš’s implicit concept of the good (informed, educated, empathic, immersed ) reader: the reader of The Attic and the reader in The Attic, the problem of duality, that is, the multiplication of identity of the author’s I and the relation between life and literature, which is an obsessive question of Kiš’s poetics. The article “The Reader with a Lamp at the Crossroads” (Kiš’s concepts of the reader and Kiš as a reader), which the author of the paper published in the previous edition of the journal Baština, deals with the status and types of readers in the poetics of Danilo Kiš, therefore, this paper represents a continuation and intensification of the research in that direction.